Unraveling the balance between personal data protection and public interest: a theoretical framework and its empirical application in personal data processing. - Jiang, Yu; Yu, Xiaolan; Qin, Youjia (Journal of Chinese Governance, 2026)
In the context of rapid technological advancement, personal data processing has become a cornerstone of data governance, while the protection of public interest has emerged as a critical challenge. This study addresses the dilemma of balancing personal data protection and public interest by reviewing the theoretical literature on public interest and proposing a three-dimensional theoretical framework. The framework integrates philosophical, legal, and social perspectives to define public interest in data processing, which is then validated through an empirical analysis of health data governance in Oxfordshire, UK, and comparative legal studies across major jurisdictions. The findings reveal that public interest in data processing is context-dependent and requires a balanced approach combining legislative clarity, ethical data sharing, and technical safeguards. This research contributes to the theoretical discourse by providing a structured model for operationalizing public interest and offers practical insights for policymakers and practitioners in data governance.